MOTIVASI BERPRESTASI ATLET PUTRI PADA CABANG OLAHRAGA FUTSAL SE-PEKANBARU - Putri Febriyanti; Ramadi '; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Problem in this research is not maximal performance of futsal inPekanbaru. It is suspected because there is no achievement motivation from the femalefutsal players. Therefore the purpose of this research was to determine the achievementmotivation from female futsal players in Pekanbaru. Population in this research were 7teams and total is 82 people with sample using purposive sampling with 3 teams that istotal is 30 people. The method used is descriptive analysis percentage. It will analyzethe problems encountered in this research regarding the “achievement motivationfemale athletes futsal in Pekanbaru. Based on the results obtained from the femaleathletes achievement motivation in sport futsal in Pekanbaru, the first indicatorsamounted 75,583%, the second indicator amounted to 83,263%, the third indicatoramounted to 74,583%. The third of indicator result is 79,36%. If we compare it with thecriteria of analysis, descriptive presentation can be classified either that the range of76-100%.Keyword: motivation and achievement